A tridentate CNO‐donor palladium(II) complex as efficient catalyst for direct C―H arylation: Application in preparation of imidazole‐based push–pull chromophores. (25th August 2017) - Li, Hui‐Hong; Maitra, Ratnava; Kuo, Ya‐Ting; Chen, Jie‐Hong; Hu, Ching‐Han; Lee, Hon Man
Abstract : A series of imidazolium chlorides for the formation of tridentate CNO‐donor palladium(II) complexes featuring N‐heterocyclic carbene moieties have been developed from cheap and readily available starting materials with high yields. Their palladium complexes were prepared by reactions between the ligand precursors and PdCl2 using K2 CO3 as base in pyridine with reasonable yields. These air‐stable metal complexes were characterized using 1 H NMR and 13 C{ 1 H} NMR spectroscopy and elemental analyses. Heteronuclear multiple bond correlation experiments were performed to identify key NMR signals of these compounds. The structures of two of the complexes were also established by single‐crystal X‐ray diffraction analysis. One of these complexes was successfully applied in the direct C―H functionalization reactions between heterocyclic compounds and aryl bromides, producing excellent yields of coupled products. The coupling reactions were scalable, allowing grams of coupled products to be obtained with a mere 2 mol% of Pd loading. The catalyst system developed allowed the large‐scale preparation of several push–pull chromophores straightforwardly. Photophysical properties based on UV–visible and fluorescence spectroscopy for these chromophores were investigated. Deep blue photoluminescence with moderate quantum efficiency and twisted intramolecular charge transfer excited state were observed for these chromophores. Density functional theory (DFT) and time‐dependent DFT calculations were performed to support the experimental results. Abstract : A tridentate CNO‐donor palladium(II) complex featuring an N‐heterocyclic carbene moiety was developed as an efficient catalyst for direct C―H arylation between heterocyclic compounds and aryl bromides. The catalyst system allowed large‐scale preparation of several push–pull chromophores straightforwardly with a mere 2 mol% of Pd loading.